Glass road (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The problem with road construction is that the work is both expensive and short-term. In the conditions of the Kyrgyz Republic, great opportunities and resources are opened up through the use of various types of stones as raw materials in the construction of roads, including highways. The stones melt at a certain temperature and can be shaped into a variety of shapes as molten glass. These two factors give rise to this new idea. The advantage of the idea is that road construction becomes much cheaper, and the service life increases several times.
Keywords: Rocks; stones; temperature; melting; glass; induction furnaces; thyristor; trigger; electric arc; electrode